Informacja statystyczna w zasilaniu organizacji przedsiębiorstwa zorientowanego procesowo - Szkic-Czech, Ewa (Statistic Information: Reinforcement of an Organization of Process Oriented Businesses, 2009)
The article discusses the problems of information as an economic source of business functioning in conditions of market globalization and competition. The author focuses on informative quality of official (public) statistic information. She considers it as a category reinforcing economic processes of a business and as a tool which enables it to improve process organization oriented on integration of a business with the market where they accomplish a chain of values. The publication underlines a practical significance of injection of statistic information supplied with (public) official statistics to a model of processes of a business, and relates this kind of information to a quality controller of results to achieve, given to our integrated model of economic organization of processes. The author proves that the model of economic processes of a business supported by statistic information increases the level of market adaptation of the business.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 251-363